Wise decisions : a science-based approach to making better choices - Loehr, James E.; Ohlsson, Sheila; Walker, Sheila Ohlsson (Ascent Audio, 2023)
A concrete and hands-on method for improving your everyday decisions Every fifteen minutes, each of us can make ten or more small decisions. Some of them are relatively inconsequential, while others can change the course of our lives. What if you could improve all of your decisions, across the board, and start to build a healthier, more productive, and meaningful life? In Wise Decisions: A Science-Based Approach to Making Better Choices, a team of accomplished industry experts delivers an evidence- and research-based blueprint for making the best decisions you can with the information you have. You'll learn to make the targeted, repeated investment of energy required to turn your decision-making process into one informed by reason, emotion, intuition, and science. In the book, you'll discover: how to put the decision-making process under a microscope and learn what makes a decision truly wise; ways to help children, teens, and families make wise decisions; and how to train yourself to make wise decisions with voice training and other strategies.